Establishing a Model to Label and Stimulate Cells Active During Motor Behaviour - Marc, Vani (Université d'Ottawa / University of Ottawa, 2018)
The remapping of cortical networks after stroke is hypothesized to be one of the mechanisms subserving functional recovery. Our understanding of cortical remapping remains limited due to the inability to resolve which cells are active while performing motor tasks with high temporal and spatial specificity. The experiments presented in the first chapter of this thesis evaluate the ability of the inducible Arc-CreERT2:Rosa-YFPf/f model to label cells in the motor cortex activated by a motor-related behaviour. Through the modification of previously published 4-hydroxytamoxifen treatment paradigms, this model can differentiate between animals that performed the rotarod task at two time points and home cage controls. In addition, 65% of cells active at the first behavioural time point are reactivated. Taken together, these data suggest that the Arc-CreERT2:Rosa-YFPf/f model is able to reliably label networks used to perform the same behavioural task at two time points. The second chapter of this thesis details a pilot study in which the Arc-CreERT2:Rosa-ChR2:YFPf/f model was used to test the effect of daily optogenetic stimulation of the contralateral cortex on functional recovery. The results of this chapter suggest that stimulating the contralesional motor cortex may impair functional recovery. Overall, the results of this thesis lay the foundation to use this model to investigate motor networks in both naïve and pathological conditions, such as stroke.
Keywords: Stroke recovery; Animal models; Optogenetics; Cortical reorganization